Data-driven estimation of the invisible energy of cosmic ray showers with the Pierre Auger Observatory - Aab, A.; Abreu, P.; Aglietta, M.; Albuquerque, I. F. M.; Albury, J. M.; Gobbi, Fabián Jesús; Bertou, Xavier Pierre Louis; Etchegoyen, Alberto; Garcia, Beatriz Elena; Mariazzi, Analisa Gabriela; Ferreyro, Luciano Pablo; González, Nicolás Martín; et al. (American Physical Society, 2019)
Fil: Aab, A.. Radboud Universiteit Nijmegen; Países Bajos